Various heuristic algorithms to minimise the two-page crossing numbers of graphs - He, Hongmei; Sălăgean, Ana; Mäkinen, Erkki; Vrt'o, Imrich (De Gruyter, 2015)
We propose several new heuristics for the twopage book crossing problem, which are based on recent algorithms for the corresponding one-page problem. Especially, the neural network model for edge allocation is combined for the first time with various one-page algorithms. We investigate the performance of the new heuristics by testing them on various benchmark test suites. It is found out that the new heuristics outperform the previously known heuristics and produce good approximations of the planar crossing number for severalwell-known graph families. We conjecture that the optimal two-page drawing of a graph represents the planar drawing of the graph.
Keywords: Heuristic algorithm; Two-page book crossing number; One-page book crossing number; Hamiltonian cycle; Planar drawing